Peningkatan Kinerja Guru Pendidikan Agama Katolik melalui Pelaksanaan Supervisi Akademik oleh Kepala Sekolah di SD Swasta Katolik Delitua - Sherly Yasinta Manalu; Johannes Sohirimon Lumbanbatu (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2023)
This research was prompted by concerns regarding the superficial nature of academic supervision conducted by principals, which in turn affected the quality of teachers' instructional performance. Consequently, the objective of this study was to examine the process of implementing academic supervision by school principals and assess the extent to which more effective supervision could enhance the performance of Catholic Religious Education teachers. The qualitative approach was employed as the research methodology. The findings indicate that the implementation of robust academic supervision by school principals can lead to improvements in teacher performance, particularly in the areas of lesson planning, instructional delivery, and assessment. Moreover, the study uncovered aspects that were not captured by the predefined assessment instruments used during supervision observations. In these instances, the principal guided teachers in identifying their own areas of improvement and provided support to address these shortcomings. Additionally, the study revealed that effective teacher performance was characterized by the promotion of critical and creative thinking among students, thus enhancing the overall quality of classroom instruction. In conclusion, the study highlights the positive impact of academic supervision conducted by principals on teachers. Through this process, teachers are encouraged to enhance their preparation and performance, resulting in notable improvements.